Comparison of classical tsunami resistance systems in RC structure - Toloue, I. (Multi-Science Publishing Co. Ltd, 2014)
The seismic performance response of reinforced concrete (RC) structures subjected to simultaneous Tsunami force and earthquake excitation is evaluated. Several classical resistance systems, such as bare frame, shear wall, steel brace, and dual systems, are employed in an eight-story RC building to resist these forces. The economic design of the systems is also considered. To satisfy the economic aspects, RC structures should utilize the minimum columns and beam size. Results show that the shear wall and bare frame systems failed because of their uneconomic properties compared with other resistance systems. On the basis of engineering and economical views, the dual system is accepted and commended among classical lateral resistance systems.